The Individual and Combined Effects of Prenatal Micronutrient Supplementations on Neurobehavioral Developmental Disorders in Preschool Children - Liwen Ding; Esben Strodl; Maolin Zhang; Weiqing Chen (Children)
Background: Neurobehavioral developmental disorders significantly affect children’s future well-being and contribute to the global disease burden. While prenatal micronutrient supplementation is crucial for fetal neural development, their individual and combined effects on subsequent neurobehavioral outcomes in childhood remain poorly understood. This study aimed to examine the individual and combined effects of prenatal micronutrient supplementation on neurobehavioral developmental disorders in preschool children, and to explore their effects across specific developmental domains. Methods: 15,636 mother-child dyads were recruited from the 2022 children’s survey in Shenzhen, China. Mothers provided information on prenatal supplementation of calcium, folic acid, iron, and multivitamins. Five domains of children’s neurobehavioral functioning were assessed using the Ages and Stages Questionnaire-Third Edition (communication, gross motor, fine motor, problem-solving, and personal-social status). Logistic regression models were used to estimate the effect of micronutrient supplementations on NDDs across crude, adjusted, and full-inclusion models. Combined effects were assessed by multiplicative and additive interactions calculated from crossover analysis. Results: 11.7% of preschool children were identified as at risk for neurobehavioral developmental disorders, with the highest prevalence in the gross motor domain. Prenatal multivitamin supplementation showed a protective effect against neurobehavioral developmental disorders (OR = 0.73, 95% CI = 0.66–0.81). Interaction analysis revealed that the combination of iron and multivitamins further enhanced this protection, with both multiplicative (IOR = 1.26, 95% CI = 1.02–1.57) and additive interactions (RERI = 0.18, 95% CI = 0.02–0.35). The problem-solving domain consistently showed the greatest benefit from the supplementation of these micronutrients individually and in combination. Conclusions: Prenatal multivitamin supplementation reduces the risk of neurobehavioral developmental disorders, especially when combined with iron supplementation. These findings highlight the potential benefits of prenatal co-supplementation strategies to improve neurobehavioral outcomes in offspring. Further studies are recommended to confirm these findings and explore underlying mechanisms.